Entrepreneurial orientation and organizational performance of online business in Malaysia: the mediating role of the knowledge management process - Adam, Sabrinah; Mohd Fuzi, Nursyazwani; Ramdan, Mohamad Rohieszan; Mat Isa, Rosmah; Ismail, Albert Feisal Muhd Feisal; Hashim, Mohd Yussni; Yong, Sharon Yee Ong; Ramlee, Shah Iskandar Fahmie (Multidisciplinary Digital Publishing Institute, 2022)
The aim of this paper is to examine the role of the knowledge management process as a mediating variable in the relationship between entrepreneurial orientation and organizational performance. This study employed a quantitative method and utilised a self-administered questionnaire. A total of 350 data were collected from the owners/founders of online businesses. A Partial Least Squares-Structural Equation Modelling (PLS-SEM) analysis was performed to test the proposed hypotheses of the study. The findings indicated that entrepreneurial orientation positively the knowledge management process, which in turn exerts a positive effect on the organizational performance of a company. Additionally, the indirect effect analysis revealed that the knowledge management process plays a significant role as a mediator between entrepreneurial orientation and organizational performance. The research fills a gap in the literature by considering a mediating variable in enhancing the relationship between entrepreneurial orientation and organizational performance. This research also provides a particular contribution to the literature and some suggestions for future research.